The leadership dimension in information and communication technology adoption in African libraries (2014)
The article focuses on leadership challenges in adaptation to Information and Communication Technologies (ICTs) in African libraries. It identifies and discusses the need for adequate leadership styles and behavior in the bid to adapt effectively to new technologies. Online survey, observation arising from personal professional practice experience, personal communication, and interview methods were used to gather data for the study. Older library professionals, many of whom are still very visible across the leadership strata of libraries, were found to exhibit diverse attitude to the adaptation to ICTs deployment and use in their libraries. Some library leaders and older generation professionals were discovered to react somewhat negatively to changes in technology used in their libraries, preventing the younger professionals from performing to full capacity, and generally showing nonchalance to new technologies. Proper training and retraining, mentoring, and harnessing the synergy of ideas, with respectful communication from new generation library professionals, was found to be desirable. Change management workshops and implementation of standard ethics of the profession are recommended, while emphasis is put on the need for library professionals to overcome their technophobia and take leadership in adapting to move the library and information profession forward.